Implementation of Problem Based Learning Model to Improve Learning Outcomes of Fourth Grade Students at SDN 1 Jamblang - Wahyu Arif Gunawan; Mimin Darmini; Sati Sati (FKIP - Universitas Riau, 2026)
The low learning outcomes of fourth-grade students at SD Negeri 1 Jamblang are the main reason for this research. This research uses a classroom action research (CAR) method with qualitative and quantitative approaches. The aim is to determine the effectiveness of the implementation of the Problem Based Learning (PBL) model in improving learning outcomes. The PBL model was chosen because it is able to encourage students to be more active, critical, and directly involved in problem solving. The results of the study showed an increase in learning outcomes at each stage. In the pre-cycle, only 5 students (15.15%) achieved the Minimum Competency (KKM) of 75. After the PBL model was implemented in cycle I, learning mastery increased to 21 students (63.63%). This increase continued in cycle II, where 30 students (90.90%) successfully achieved mastery. Based on these results, it can be concluded that the implementation of the Problem Based Learning model has proven effective in improving the activeness and learning outcomes of fourth-grade students, so this model is suitable for use as an alternative in efforts to improve the quality of learning in the classroom.